Exploitation of some raw minerals for Increasing productivity of ordinary portland cement. - Khalil, N. M.; Algamal, Yousif Mohamed (Archives of Business Research, 2018)
This study aims to utilize a local natural mineral material from different places in western area of Saudi Arabia namely, (Osfan, Alkamel, Wadi starah, Khulais, Jeddah and Alghowla) as a partial replacement of ordinary portland cement (OPC) in order to increase the productivity of ordinary portland cement (OPC), minimizing the problems associated with its industry involving energy consumption and air pollution. In addition to the reference sample (C:100% wt. OPC), other six mixes were prepared from 75% wt. of OPC and 25 wt. %) of each raw mineral, they are denoted as (C1, C2, C3, C4, C5 and C6). Different cementing, sintering, chemical and mechanical properties of the prepared mixes were tested according to the international standard specifications. It was concluded that OPC blended with 25 wt.% of local natural minerals from Jeddah (C5), Wadi starah (C3) and Alkamel C2 show outstanding cementing and mechanical properties compared with the reference sample. They recorded relatively longer setting time ranges from (55-160, 52-145, 52-144) minutes compared with the reference sample (C) which recorded only (48-120) minutes, relatively higher percent of combined water at different ages of hydration (23.75-28.23, 20.84-24.59, 16.34-19.31%),respectively whereas the reference sample (C) recorded (15.59-18,00 %), higher heat of hydration (81-97, 77-94, 75-90 cal/g), respectively compared with reference sample which recorded (70- 85 cal/g ), higher bulk density (1.61-1.96, 1.66-1.84, 1.65-1.84 g/cm3), respectively compared with the reference sample that recorded (1.61-1.84 g/cm3), lower apparent porosity (15.02-10.41, 16.25-12.75, 17.40-13.96%), respectively whereas the reference sample noted (24.11-14.39%) and relatively higher values of compressive strength (90-125, 80-120, 75-113 kg/cm2), respectively compared with the reference sample which recorded (60-110 kg/cm2). The remaining samples C1, C4 and C6 showed less cementing and mechanical properties compared with the reference sample (C). The improved properties of C5, C3 and C2 are due to their relatively higher content of portlandite mineral (Ca(OH2)) one of the main hydration of cement, as well as their relatively better microstructure.